Manufacturing sector's growth in Tanzania: Empirical lessons from macroeconomic factors, 1970–2021 - Lutengano Mwinuka; Veronica Claud Mwangoka (Cogent Economics & Finance, 2023)
The study investigates the Tanzania manufacturing sector's growth with a view to provide empirical lessons from macroeconomic factors with limited political regimes reflections. A vector error collection model was used to assess the influence of foreign direct investments (FDI), inflation (INF), export of product (EXP), power supply (PS), government expenditure (GoE), nominal lending interest rate (IRL), population growth rate (PGR) and exchange rate (EXR). The estimated value of the coefficient measuring the speed of adjustment toward long-run equilibrium is statistically significant and negative, implying that 41.6% of the short-run shocks can be corrected back to the long-run equilibrium immediately in the following year so has to prevent the model from explosion. Signs of INF, PS and IRL in the model estimation conform to expectations. Moreover, reducing production costs, increasing the trade openness, attracting FDI, offering appropriate government incentives and management of the foreign exchange rate have potentials of boosting the Tanzania's economic growth. Thus, the government in collaboration with other stakeholders should work toward making the Tanzania manufacturing sector's growth more competitive by creating conducive business environment that will lead to multiplier effects.
Keywords: 330; competitiveness; conducive business environment; macroeconomic variables; political settlement